Amh regulate female folliculogenesis and fertility in a dose-dependent manner through Amhr2 in Nile tilapia. (1st January 2020) - Liu, Xingyong; Xiao, Hesheng; Jie, Mimi; Dai, Shengfei; Wu, Xin; Li, Minghui; Wang, Deshou
Abstract: In the present study, Amh was found to be abundantly expressed in the granulosa cells of the primary growth follicles, and Amhr2 in the granulosa cells, oogonia and phase I oocytes in tilapia by immunohistochemistry. In addition, Amh and Amhr2 were also found to be expressed in the brain and pituitary. Heterozygous mutation of either amh or amhr2 resulted in increased primary growth follicles and decreased fertility, and homozygous mutation resulted in hypertrophic ovaries with significantly increased primary follicles and failed transition from primary to vitellogenic follicles. Expression of gnrh3 in the brain, fsh and lh in the pituitary and serum E2 concentration were significantly decreased in both mutants. Significantly increased apoptosis of follicle cells was observed in both mutants. However, administration of E2 failed to rescue the folliculogenesis defects of the mutants. Our results suggested that Amh acts in a dose-dependent manner by binding Amhr2 in tilapia. Highlights: Amh signaling is Amhr2 dependent in teleosts. Homozygous mutation resulted in excessive proliferation of germ cells. Homozygous mutants failed to transition from primary to vitellogenic follicles. Increased apoptosis of follicle cells in both amh and amhr2 mutants.